Diritti negoziati. Trasformazioni sociali e pratiche giuridiche - Patrizia Resta (EtnoAntropologia)
This introduction discusses the rhetoric of the 'rule of law'. Based on various ethnographies, it reflect on negotiating order to which legal and illegal definitions are subject in the practice of social agents. The aim is to demonstrate the effectiveness of the legal anthropological perspective in eradicating the legal monism and in discussing the hegemony of rule of law, shifting attention to the plurality of normative available to rights holders. The paper focuses on the interstices between law and politics and on the new issues that have arisen in the contemporary. These require an openness to an idea of law less dogmatic and hegemonic and therefore flexible, dialogic and negotiated.